GROWTH PARAMETERS AND VITAMIN D STATUS IN CHILDREN WITH THALASSEMIA MAJOR IN UPPER EGYPT. - Fahim M. Fahim; Khaled Saad (Mediterranean Journal of Hematology and Infectious Diseases, 2014)
Aim: the aim of this study is to assess the growth parameters, vitamin D, calcium, and phosphorous status in children with thalassemia major receiving packed red cells transfusion with chelation therapy.